COSIMO – patients with active cancer changing to rivaroxaban for the treatment and prevention of recurrent venous thromboembolism: a non-interventional study - Alexander T. Cohen; Anthony Maraveyas; Jan Beyer-Westendorf; Agnes Y. Y. Lee; Lorenzo G. Mantovani; Miriam Bach; on behalf of the COSIMO Investigators (Thrombosis Journal, 2018)
Abstract Background Around 20% of venous thromboembolism (VTE) cases occur in patients with cancer. Current guidelines recommend low molecular weight heparin (LMWH) as the preferred anticoagulant for VTE treatment. However, some guidelines state that vitamin K antagonists (VKAs) and direct oral anticoagulants (DOACs) are acceptable alternatives for long-term therapy in some patients if LMWHs are not available. LMWHs and VKAs have a number of drawbacks that can increase the burden on patients. DOACs, such as rivaroxaban, can ameliorate some burdens and may offer an opportunity to increase patient satisfaction and health-related quality of life (HRQoL). The Cancer-associated thrOmboSIs – patient-reported outcoMes with rivarOxaban (COSIMO) study is designed to provide real-world information on treatment satisfaction in patients with active cancer who switch from LMWH or VKA to rivaroxaban for the treatment of acute VTE or to prevent recurrent VTE. Methods COSIMO is a prospective, non-interventional, single-arm cohort study that aims to recruit 500 patients in Europe, Canada and Australia. Adults with active cancer who are switching to rivaroxaban having received LMWH/VKA for the treatment and secondary prevention of recurrent VTE for at least the previous 4 weeks are eligible. Patients will be followed for 6 months. The primary outcome is treatment satisfaction assessed as change in the Anti-Clot Treatment Scale (ACTS) Burdens score at week 4 after enrolment compared with baseline. Secondary outcomes include treatment preferences, measured using a discrete choice experiment, change in ACTS Burdens score at months 3 and 6, and change in HRQoL (assessed using the Functional Assessment of Chronic Illness Therapy – Fatigue questionnaire). COSIMO will collect data on patients’ medical history, patterns of anticoagulant use and incidence of bleeding and thromboembolic events. Study recruitment started in autumn 2016. Conclusions COSIMO will provide information on outcomes associated with switching from LMWH or VKA therapy to rivaroxaban for the treatment or secondary prevention of cancer-associated thrombosis in a real-life setting. The key goal is to assess whether there is a change in patient-reported treatment satisfaction. In addition, COSIMO will facilitate the evaluation of the safety and effectiveness of rivaroxaban in preventing recurrent VTE in this patient population. Trial registration NCT02742623. Registered 19 April 2016.